Le aspettative finzionali: una nuova analisi della dinamica del capitalismo - Andrea Declich (Quaderni di Sociologia, 2019)
The article presents Imagined Futures. Fictional Expectations and Capitalist Dynamics by economic sociologist Jens Beckert and the main concepts he proposes, particularly that of “Fictional Expectation”, as well as the path followed for coming to its definition. The book focuses on the issue of the temporal nature of social and economic action, and the connected fundamental problem of uncertainty of the future. Dealing with these issues is a challenge for economic sociology and for economics, as well as for all the social sciences. The author addresses the challenge through an interdisciplinary approach, that also resorts to literature and narrative theory in order to deal with the fictional nature of expectations. Beckert’s book has not been translated into Italian but it has been widely read and appreciated overseas (some reviewers say it could become a “modern classic” of economic sociology). The article also addresses some of the issues that have emerged from the debate that followed the publishing of the book.